Utilização de bioensaios para avaliação da ecotoxicidade em resíduos de esgotamento de caminhão limpa- fossa: lodo de fossa séptica - Vasconcelos, Geísa Vieira (2012)
A way to recycle the nutrients and organic matter from sewage sludge from septic tanks and cesspools would return those elements to biogeochemical cycles. The agricultural use of sewage sludge is an alternative that provides environmental benefits when compared to other final disposal practices and its application in soil can bring benefits to agriculture. The present study aimed to evaluate the acute toxicity of clean trucks (septic sludge) from different homes through the use of bioassays, with three bodies bioindicators of toxicity, the microcrustaceans (Daphnia magna and Daphnia similis) and bacteria (Vibrio fischeri) in the Microtox ® System. First was made the physico-chemical, microbiological characterization and heavy metals waste exhausted clean trucks and trench-toxicity tests were carried out at a later date. The collections were held fortnightly in the ETE São Cristóvão, where samples were brought to the laboratory to perform the analyses of pH, alkalinity, temperature, electrical conductivity, solids, BOD, COD, nitrogen, phosphorus and termotolerantes coliforms. It was noted that such waste presented well concentrations higher than those of domestic sewage and also features plenty of variables. The volatile fraction accounts for around 65% of total solids and SV/ST was 0.6, indicating that the septic tanks and septic sludge can be considered stable according to the CONAMA 375/2006. Were also conducted analyses of heavy metals (Cadmium, chromium, manganese, nickel, zinc, lead, iron and copper) to verify that had some correlation with toxicity. All samples clean truck depleted-fossa showed acute toxicity for microorganism three Daphnia magna, Daphnia similis, and Vibrio fischeri averaging equal to 54%, EC50 41% 52% respectively, all of which are considered toxic. With respect to sensitivity to Daphnia similis was the body that has greater sensitivity to septic waste, because the lower the EC50 is more toxic to sample. By the results obtained, the clean trucks waste-fossa are toxic and could not be used in agriculture without a prior treatment for the removal of toxicity.